THE RELATIONSHIP BETWEEN SELF-CONTROL AND CONFORMITY WITH ACADEMIC PROCRASTINATION OF STUDENT UNIVERSITY IN JAKARTA - Maulida, Jauza; Karyaningsih, RR Ponco Dewi; Sudiyarto, Dadang (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This study aims to determine the relationship between self-control (X1) and conformity (X2) with academic procrastination (Y) in students. Researchers conducted quantitative research methods using a descriptive approach. The population used in this study were students with a sample of 196 students. The sampling technique used proportional random sampling. The data analysis technique used SPSS version 25. Based on the requirements analysis test, the data are normally distributed and have a linear relationship. From the results of the F test in the ANOVA table, Fcount 117.994 > Ftable 3.04, it means that self-control and conformity are simultaneously related to the academic procrastination variable. The t-test results in tcount X1 (-5.699) <-ttable value of (-1.97233) because tcount > ttable, it can be concluded that there is a negative relationship between self-control and academic procrastination. Furthermore, tcount X2 14.850 > ttable 1.9723 because tcount > ttable, it can be concluded that there is a positive relationship between conformity and academic procrastination. Then the coefficient of determination test was obtained 0.550 meaning that the relationship between self-control and conformity with academic procrastination was 55% and the remaining 45% was influenced by other variables not examined.